2016
DOI: 10.1111/mec.13754
|View full text |Cite
|
Sign up to set email alerts
|

Mixed population genomics support for the central marginal hypothesis across the invasive range of the cane toad (Rhinella marina) in Australia

Abstract: Understanding factors that cause species’ geographic range limits is a major focus in ecology and evolution. The central marginal hypothesis (CMH) predicts that species cannot adapt to conditions beyond current geographic range edges because genetic diversity decreases from core to edge due to smaller, more isolated edge populations. We employed a population genomics framework using 24,235-33,112 SNP loci to test major predictions of the CMH in the ongoing invasion of the cane toad (Rhinella marina) in Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 87 publications
(274 reference statements)
7
54
2
Order By: Relevance
“…In their review, Pironon et al () pointed out that such correlations are far from universal and suggested that colonization dynamics may play a more important role than ecological suitability in shaping patterns of genetic diversity. Similar conclusions have been reached by a number of studies for a variety of taxa (Soares et al , Duncan et al , Ortego et al , Pironon et al , Trumbo et al ). In A. l. lyrata clear support for an association between genomic diversity and range position, with only limited evidence of an association between genomic diversity and environmental suitability, suggests that colonization dynamics may have been the main factor shaping genetic diversity in this system as well.…”
Section: Discussionsupporting
confidence: 84%
“…In their review, Pironon et al () pointed out that such correlations are far from universal and suggested that colonization dynamics may play a more important role than ecological suitability in shaping patterns of genetic diversity. Similar conclusions have been reached by a number of studies for a variety of taxa (Soares et al , Duncan et al , Ortego et al , Pironon et al , Trumbo et al ). In A. l. lyrata clear support for an association between genomic diversity and range position, with only limited evidence of an association between genomic diversity and environmental suitability, suggests that colonization dynamics may have been the main factor shaping genetic diversity in this system as well.…”
Section: Discussionsupporting
confidence: 84%
“…Theory and some empirical evidence suggest that directional selection may be particularly pronounced at species’ range limits where environments tend to be less optimal for growth and reproduction (Kirkpatrick & Barton, ; Lancaster, ; Warren et al., ). In addition to lower habitat suitability, range limits are typically characterized by stochastic genetic and population dynamics due to lower effective population sizes ( N e ), which might increase genetic drift and thereby among‐population genetic differentiation (Swaegers et al., ; Trumbo et al., ). Due to gene flow from populations adapted to conditions in the range core, peripheral, range limit populations are expected to be maladapted relative to core populations (Bridle & Vines, ; Kirkpatrick & Barton, ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of population genetic patterns across a species' geographical range is of crucial importance to predict its responses to climate change (MacArthur, ; Trumbo et al, ). As one of the major evolutionary hypotheses, the central–marginal hypothesis (CMH) makes specific predictions in this regard (Eckert, Samis, & Lougheed, ; Sexton, McIntyre, Angert, & Rice, ).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the major evolutionary hypotheses, the central–marginal hypothesis (CMH) makes specific predictions in this regard (Eckert, Samis, & Lougheed, ; Sexton, McIntyre, Angert, & Rice, ). It predicts that geographically peripheral populations should exhibit reduced genetic diversity and increased genetic differentiation than central populations due to smaller effective population size and stronger geographical isolation (Eckert et al, ; Trumbo et al, ). If this is true, peripheral populations will have limited evolutionary potential to adapt to habitat conditions beyond current range limits.…”
Section: Introductionmentioning
confidence: 99%